The effect of carbonated beverage to the discoloration of polished and unpolished nanohybrid composite resin - Hany Maghfiroh; Raditya Nugroho; Niken Probosari (DiscoverSys Inc., 2016)
Nanohybrid resin composite is one of the restorative dental materials that has goodaesthetic value and smooth surface. However, resin composite can be discolored due toconsuming foods and beverages, one of which is a carbonated beverage. To determineÂ the difference of discoloration of polished and unpolished nanohybrid resin compositeafter the immersion in carbonated beverage. An experimental laboratories research withthe post test only control group design. In the group of polished composite, polishing wasdone on one side only, while the unpolished composit group, any treatment wasn't done.The total were 32 samples, divided into 4 groups which were immersed in carbonatedbeverages and artificial saliva for 7 days. The shredded material was replaced every 24hours. The instrument used for testing the discoloration was a spectrophotometer. Datawas analyzed by parametric statistical test One-way ANOVA and LSD (Least SignificantDifferent). There were significant differences between the unpolished composite resin thatsoaked in carbonated beverages and the other groups (p <0.05). Unpolished resincomposite are prone to discolorate compared to the polished resin composite